Evaluation of aging, diabetes mellitus, and skin wounds by scanning acoustic microscopy with protease digestion. Issue 1 (1st January 2018) - Miura, Katsutoshi; Yamashita, Kanna
ABSTRACT: Scanning acoustic microscopy (SAM) can assess tissue stiffness by calculating the speed of sound (SOS) through tissues. SOS increases as tissue stiffness increases. Sensitivity to protease digestion depends on protein type, concentration, and modification. We analyzed the SOS images of formalin-fixed paraffin-embedded skin sections from elderly, young, diabetic, and nondiabetic subjects, as well as chronic and acute wounds. SAM provided high-resolution histology similar to LM and revealed characteristic SOS alteration following pepsin treatment. SOS values of dermis samples from elderly subjects (especially females) were lower than those of younger adults, which was indicative of age-related dermal softening and loosening. SOS values of elderly females were lower than those of younger females and elderly males. Dermal SOS showed a positive correlation with epidermal thickness. SOS values of epidermis of elderly subjects were higher than those of younger adults and showed a rapid decline 0.5h after protease digestion. Reticular dermis of diabetic patients exhibited greater pepsin resistance than that of nondiabetic patients. Chronic wounds exhibited greater SOS values and pepsin resistance than acute wounds. SOS variation with aging, diabetes mellitus, and wound fibrosis reflected histological and mechanical changes associated with senescence and disease duration. Epidermal thickness reflects age-related changes in dermal stiffness.